Colchicine and risk of hospitalization due to COVID‐19: A population‐based study. Issue 2 (22nd January 2023) - Sáenz‐Aldea, María; Salgado‐Barreira, Ángel; Taracido Trunk, Margarita; Piñeiro‐Lamas, María; Herdeiro, Maria T.; Portela‐Romero, Manuel; Saez, Marc; Figueiras, Adolfo
Abstract: Colchicine is one of the most widely studied and best‐known anti‐inflammatory treatments. This study aimed to assess the effect of colchicine on risk of hospitalization due to COVID‐19; and its effect on susceptibility to and severity of the virus in patients with COVID‐19. We carried out a population‐based case‐control study. The following groups were applied: (1) to assess risk of hospitalization, cases were patients with a positive PCR who were hospitalized due to COVID‐19, and controls without a positive PCR; (2) to assess susceptibility to COVID‐19, cases were patients with a positive PCR (hospitalized and non‐hospitalized), and the same controls; (3) to determine potential severity, cases were subjects with COVID‐19 hospitalized, and controls patients with COVID‐19 nonhospitalised. Different electronic, linked, administrative health and clinical databases were used to extract data on sociodemographic variables, comorbidities, and medications dispensed. The study covered 3060 subjects with a positive PCR who were hospitalized, 26 757 with a positive PCR who were not hospitalized, and 56 785 healthy controls. After adjustment for sociodemographic variables, comorbidities and other treatments, colchicine did not modify risk of hospitalization due to COVID‐19 (adjusted odd ratio [OR] 1.08 [95% confidence interval (CI) 0.76−1.53]), patients' susceptibility to contracting the disease (adjusted OR 1.12 (95% CI 0.91−1.37)) or the severity of the infection (adjusted OR 1.03 [95% CI 0.67−1.59]). Our results would neither support the prophylactic use of colchicine for prevention of the infection or hospitalization in any type of patient, nor justify the withdrawal of colchicine treatment due to a higher risk of contracting COVID‐19.